BRCA2-dependent and independent formation of RAD51 nuclear foci. - Tarsounas, M; Davies, D; West, S (2003)
The formation of RAD51 foci in response to ionizing radiation (IR) represents an important step in the repair of DNA double-strand breaks. RAD51 foci also appear during S phase and are thought to be required for the restart of stalled or broken replication forks. The RAD51 recombinase interacts directly with the breast cancer-associated tumour suppressor BRCA2, an interaction that is required for normal recombination proficiency, radiation resistance and genome stability. In CAPAN-1 cells, which express a truncated form of BRCA2 that is cytoplasmic because of loss of the nuclear localization signal, the formation of IR-induced RAD51 foci is impaired. In this work, we show that S-phase RAD51 foci form normally in CAPAN-1 cells expressing truncated BRCA2. Moreover, we find that RAD51 specifically associates with chromatin at S phase in a reaction that is BRCA2-independent. The observed BRCA2-dependent and independent formation of RAD51 foci shows that intact BRCA2 is not required for RAD51 focus formation per se, leading us to suggest that S phase and IR-induced RAD51 foci assemble by distinct pathways with defined protein requirements.